2018
DOI: 10.1007/s00394-018-1635-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional association of dietary water intakes and sources, and adiposity: National Adult Nutrition Survey, the Republic of Ireland

Abstract: Consumption of drinking water and food moisture and not total water or beverage moisture were inversely associated with adiposity, independent of energy intake and expenditure. Advice encouraging drinking water and food moisture intake may be beneficial in addition to energy balance advice, in combating obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…They reported that replacement of milk, juice or SSBs with water resulted in lower energy intakes and greater weight loss. Most recently, Walton et al 42 reported that the Irish adults in the highest tertile of drinking water consumption had lower mean BMIs when compared to the lowest tertile of consumers, after adjustment for SES, diet quality and energy intake (β coefficient = −0.65 [CI: −1.30, −0.01]). Unfortunately, direct comparisons between the results reported herein and those of other studies are limited by the fact that water was combined with other SFB in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that replacement of milk, juice or SSBs with water resulted in lower energy intakes and greater weight loss. Most recently, Walton et al 42 reported that the Irish adults in the highest tertile of drinking water consumption had lower mean BMIs when compared to the lowest tertile of consumers, after adjustment for SES, diet quality and energy intake (β coefficient = −0.65 [CI: −1.30, −0.01]). Unfortunately, direct comparisons between the results reported herein and those of other studies are limited by the fact that water was combined with other SFB in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using a two‐tailed test to detect a 1‐unit difference in the AMED score between two independent groups and considering a significance level of 5%, a statistical power of 80%, and an AMED standard deviation of 1.6. [ 22 ] To allow for losses of follow‐up, the recruitment target was set to 98 and a total of 107 participants were recruited. Secondary outcomes were health biomarkers from lipid (TC, low‐density lipoprotein [LDL]‐cholesterol, high‐density lipoprotein [HDL]‐cholesterol, triacylglycerol, triacylglycerol‐glucose index [TyG index]) and glycemic (glucose, insulin, homeostatic model assessment for insulin resistance [HOMA‐IR]) parameters, anthropometry (weight, BMI, waist circumference, waist–hip ratio), systolic and diastolic blood pressure, blood metabolites levels using metabolomic analysis, and dietary quality assessed by the Alternative Healthy Eating Index 2010 (AHEI) [ 23 ] at week 12.…”
Section: Methodsmentioning
confidence: 99%
“…Рекомендуемое потребление железа для женщин репродуктивного возраста варьируется от 14,8 до 20 мг/сут в зависимости от страны [23]. За последние 15 лет было проведено несколько европейских исследований [21,24,25] и национальных мониторинговых исследований [26][27][28][29] по потреблению железа в репродуктивном возрасте, которые показали, что большинство женщин не потребляли рекомендуемые дозы железа. Медиана концентрации СФ колебалась от 26 до 38 мкг/л, что позволяет предположить, что в большинстве стран около 40-50% женщин репродуктивного возраста могут иметь небольшие или истощенные запасы железа [30].…”
Section: железодефицит и беременностьunclassified